A Comparative Study of Water and Land Based Exercises Training Program on Stability and Range of Motion - Hossein Abadi, Fariba; Ai Choo, Lee; Sankaravel, Mohansundar; Mondam, Srinivas (International Journal of Engineering and Technology, 2018)
Serious ankle injuries continue to be a strong concern to athletes of many sports. The frequency of ankle injuries in sport is paramount. The sports which involve the lower limbs usually will cause injuries around ankle and leading to ankle instability as a result recurrences are very common. Moreover, stability plays an important role in preventing ankle injury for an athlete. Thus, this study was aimed to identify the influence of exercises in different environments like water-based and land-based exercise over dynamic stability and range of motion (ROM) there by to prevent ankle injuries among collegiate athletes. A total of 24 amateur athletes who had ankle sprain during their sporting activities were recruited for this study and randomly assigned in two groups; water-based (BMI 23.08Â±3.17 kg.m-2) and land-based (BMI 23.94Â±4.86 kg.m-2). The exercises session were carried out twice per week, 45 minutes to an hour for 8 weeks. Both groups underwent eight weeks of training for the aquatic and land exercises. The changes (by pre and post-test) in dynamic balance were measured for both groups via Star Excursion Balance Test (SEBT) for the injured legs. The results shows pre and post-test means differences of SEBT test of water and land-based exercises groups were -5.26 Â± 1.5 and -3.77Â±1.94 cm, respectively. While there was statistically no significant differences in improvement of dynamic balance between the exercise given in both media (t=0.36; p=0.72); post-test results of both groups showed significant improvement in both groups p<0.00.Â There was only significant differences in ROM between water-based and land-based groups (t=5.37, p=0.000). This study was concluded that water and land-based exercises are useful to improve the stability and range of motion and thereby to prevent ankle injuries.Â Â